JBRMR 2017
DOI: 10.24052/jbrmr/v12is01/teoeomotqmaocotspatf
|View full text |Cite
|
Sign up to set email alerts
|

The effect of entrepreneurial orientation, market orientation, total quality management and organizational culture on the SMEs performance: A theoretical framework

Abstract: In the contemporary, Entrepreneurial orientation and Market orientation have become important topics among business academics and practitioners. Since business environment has become more competitive, the need to develop and improve internal resources is now a prerequisite for global survival; entrepreneurial orientation and market orientation are now the crucial falcons that are assisting the firms to achieve such a niche. Despite the importance of MO and EO, researches that link these concepts to SMEs perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 118 publications
(98 reference statements)
2
27
0
Order By: Relevance
“…However, a review of the literature indicates several research gaps. Most of the empirical studies on TQM and OC–performance relationships have been conducted in large enterprises especially in developed countries, while few studies have been reported in developing countries (Sinha and Dhall, 2018; Ali et al , 2017; Ebrahimi and Sadeghi, 2013), and no such research has been undertaken in KSA. This includes manufacturing-based SMEs, considered a major driver of growth in the manufacturing sector of KSA.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a review of the literature indicates several research gaps. Most of the empirical studies on TQM and OC–performance relationships have been conducted in large enterprises especially in developed countries, while few studies have been reported in developing countries (Sinha and Dhall, 2018; Ali et al , 2017; Ebrahimi and Sadeghi, 2013), and no such research has been undertaken in KSA. This includes manufacturing-based SMEs, considered a major driver of growth in the manufacturing sector of KSA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, there is a deep inherent need to investigate the association between TQM, culture and performance (Ebrahimi and Sadeghi, 2013). However, there is a lack of empirical studies examining the association between TQM and performance within the context of small and medium enterprises (SMEs), particularly in developing countries (Sahoo and Yadav, 2018; Ali et al , 2017; Ebrahimi and Sadeghi, 2013). This research addresses this case by examining the links among TQM, OC and SMEs’ performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the global performance benefits of these factors are questionable (Kober et al, 2012;Duarte et al, 2011;George, 2011;Morgan et al, 2009;Stam and Elfring, 2008) and remain inconspicuous on whether adopting EO, MO and TQM is suitable for all firms at all times. In particular, the empirical studies that examined the three constructs that may simultaneously affect business performance are limited (Ali et al, 2017;Cadogan, 2012;Hakala, 2011;Grinstein, 2008;Demirbag et al, 2006). The essential linkage of EO, MO, TQM and organisational performance in developed countries has received significant attention from practitioners and scholars (Rodr ıguez-Guti errez and Tejada, 2015;Herzallah et al., 2014;Brouthers et al, 2014;Laukkanen et al, 2013;Raju et al, 2011;Salaheldin, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In innovative SMEs, most competence management studies deal with the organizational level (Hewitt-Dundas, 2006;Hervas-Oliver et al, 2016;Ali et al, 2017;Curado, 2018;Adla et al, 2020;Saunila, 2020). In particular, strategic management researchers agree that companies obtain and maintain their competitive advantage through their ability to renew and integrate their competences and develop new ones (Teece et al, 1997).…”
Section: Organizational Level Of Competence Managementmentioning
confidence: 99%
“…Some research has sought to improve the methodology for understanding and identifying the competences necessary for the development of innovative SMEs (Danneels, 2002;Belderbos et al, 2004;Trott, 2005), but, while such studies emphasized the importance of competences, they do not provide a multilevel approach. Instead, they focus on the individual level, with entrepreneurs' individual competences (Man et al, 2002;Edwards-Schachter et al, 2015;Hero et al, 2017), the team level, with entrepreneurial team collective competences (Ruiz-Jim enez and del Mar Fuentes-Fuentes, 2016) and the organization level, with SME organizational and inter-organizational competences (Hewitt-Dundas, 2006;Hervas-Oliver et al, 2016;Ali et al, 2017;Curado, 2018;Saunila, 2020). Studying interlevel dynamics is essential in identifying the role played by each level in the successful development of innovative SMEs and in highlighting the practices used to deploy competences in such businesses.…”
Section: Introductionmentioning
confidence: 99%